Students’ satisfaction in campus cafeterias: an empirical study on public universities at Klang Valley in Malaysia - Afroza, Kaniz; Haque, A. K. M. Ahasanul; Islam, Mohammad Serazul (Southern Academic Publisher, 2022)
Cafeteria facilities are a key component of a wholesome arrangement that impacts personal happiness for both native and foreign students. For university students, the first option for dining is on-campus food services which imply the importance of the quality of the cafeteria service and must be reviewed and improved regularly. Considering the importance of students’ satisfaction this study was conducted to investigate the link between variables such as pricing, food quality, customer service, and the atmos- phere of students’ satisfaction. The convenience sampling method was used to collect quantitative data from 250 students at public universities in Klang valley of Malaysia which are IIUM, UPM, UM, UiTM, UKM and UTM. The survey was conducted via google form in September 2021. For the data analysis, descriptive, reliability, exploratory factor analysis and regression analysis have been conducted by using SPSS. The study revealed that students’ satisfaction was associated with the four independent variables. All the factors had a significant and positive influence on students’ satisfaction. From the regression analysis, it was found that customer service and price fairness had the most significant influence over student satisfaction which was followed closely by the other two variables which were food quality and atmosphere. It was also concluded that all of the independent factors included in the study had a sub- stantial influence on the dependent variable, which was student satisfaction.